Geographic Information System for Mapping Polling Station Locations in Parungkuda District - Somantri; Kamdan; Mulyana, Azril (Politeknik Piksi Ganesha Indonesia, 2023)
This study aims to develop a Geographic Information System (GIS) that maps the locations of Polling Stations (TPS) for general elections in Parungkuda District. Through literature review, field observations, and interviews with relevant stakeholders, geographical data such as TPS locations and district boundaries were collected and analyzed. In this research, a web-based information system was developed using Mapbox technology to display interactive mapping of the TPS. The outcome is a system that facilitates the public in finding TPS locations and obtaining information on the number of voters and presidential candidates in each TPS. This research has benefits in terms of mapping and accessing TPS-related information, and it is recommended for further development to be widely used in general elections within Parungkuda District. This GIS can improve the efficiency of the election process and provide ease of access for voters to find the appropriate TPS based on their residence.